Comparative Studies of Oxygen‐Free Semiconductors in Photocatalytic CO2 Reduction and Alcohol Degradation. Issue 11 (30th August 2022) - Lorenz, Felix; Moustakas, Nikolaos G.; Peppel, Tim; Strunk, Jennifer
Abstract: Commercially available α ‐SiC, β ‐SiC, GaN, ZnTe and self‐synthesized g‐C3 N4 were investigated in a comparative study regarding their photocatalytic capabilities in CO2 reduction and alcohol degradation. Under reproducible high‐purity solid‐gas conditions none of the tested materials promoted CO2 reduction using H2 O as proton donor, although TiO2 P25 has been shown to produce significant amounts of CH4 under similar conditions. Replacing H2 O with 2‐propanol led to hydrocarbon formation which could solely be attributed to alcohol degradation while no CO2 reduction took place. Abstract : Common commercially available oxygen‐free semiconductors and TiO2 were compared in gas‐solid photocatalytic CO2 reduction under reproducible high‐purity conditions. All oxygen‐free semiconductors were found inactive towards photoreduction of diluted CO2 with H2 O as a proton donor, while being active in degradation of 2‐propanol.